A functional binder–sulfonated poly(ether ether ketone) for sulfur cathode of Li–S batteries. Issue 81 (16th August 2016) - Cheng, Meng; Li, Longyan; Chen, Yanxiao; Guo, Xiaodong; Zhong, Benhe
Abstract : Sulfonated poly(ether ether ketone) (SPEEK) with strong electronegativity and adhesion ability of S/C compounds was prepared by a homogeneous reaction as the binder for the sulfur cathode of Li–S batteries compared to the conventional polyvinylidene fluoride (PVDF) binder. Abstract : Sulfonated poly(ether ether ketone) (SPEEK) with strong electronegativity and adhesion ability of S/C compounds was prepared by a homogeneous reaction as the binder for the sulfur cathode of Li–S batteries compared to the conventional polyvinylidene fluoride (PVDF) binder. The binder and its applications to lithium sulfur batteries were characterized by proton nuclear magnetic resonance ( 1 H NMR) spectroscopy, Fourier transformation infrared spectroscopy (FT-IR), thermogravimetry (TG), X-ray diffraction (XRD), scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), cyclic voltammogram (CV) and charge–discharge tests. The results show that this functional binder exhibits promising characteristics for lithium sulfur batteries with a capacity of 552.6 mA h g −1 at a current density of 1600 mA g −1 and 268.5 mA h g −1 at 1000 mA g −1 after 300 cycles.